A method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous waste
By composting, magnetic separation, rinsing and ultrasonic melting of the solid waste generated during incineration, combined with heat treatment and addition of silicon aerogel layer, the problems of solid waste disposal and environmental pollution are solved. The obtained aluminum silicate fiber cotton has excellent thermal insulation and mechanical properties.
Patent Information
- Application Number
- CN202410445553.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-15
AI Technical Summary
Improper disposal of solid waste such as fly ash, slag coarse sand, bauxite slag and coal gangue generated during incineration leads to environmental pollution and it is difficult for the existing technology to effectively utilize these wastes.
Ultrasonic melting is performed after compounding, magnetic separation, rinsing pretreatment, heat treatment gradient is set, fiber formation is performed, and a silicon aerogel layer is added to the fiber surface to enhance its hydrophobicity and toughness.
The produced aluminum silicate fiber cotton has good thermal insulation performance, high toughness, is not easy to break and produce debris, and reduces environmental pollution through efficient treatment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid and hazardous waste treatment, and in particular to a method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous waste. Background Art
[0002] Aluminum silicate fiber is a new, lightweight, energy-saving refractory material with the characteristics of high temperature resistance, good thermal stability, and mechanical vibration resistance. It is widely used in fiber felt, fiber blanket and other products, and is a new material to replace asbestos. However, it is brittle and easily produces more dust and fine fibers, which has a certain impact on human health when used.
[0003] The waste-to-energy technology in incineration is to burn the waste in an incinerator and recover the waste heat to generate electricity. It is an effective way of harmless and resource-based utilization. my country's waste-to-energy enterprises are developing rapidly, and the amount of fly ash captured during incineration and the fly ash deposited at the bottom of the flue and chimney is huge. If the solid wastes including fly ash, slag, coarse sand, bauxite slag and coal gangue are not properly disposed, they will pollute groundwater, soil and air, bringing huge environmental risks to the local area. Summary of the invention
[0004] The purpose of the present invention is to provide a method for producing aluminum silicate fiber cotton by synergistic resource utilization of solid and hazardous wastes, so as to solve the problems raised in the background technology. Solid wastes such as fly ash, slag coarse sand, bauxite slag and coal gangue are compounded, subjected to magnetic separation and leaching pretreatment, and then ultrasonically melted. After setting a heat treatment gradient, fiberization is carried out, the flue gas is treated, and a layer of silicon aerogel is added to the surface of the obtained fiber to enhance its hydrophobicity and toughness. By combining ultrasonic treatment during the heat treatment process, the toughness of the aluminum silicate fiber can be improved, and the required melting time and melting temperature can be reduced. The aluminum silicate fiber cotton obtained has the advantages of good thermal insulation performance, high toughness, and is not easy to break and produce debris.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous wastes comprises the following steps:
[0007] S1. Compounding the composite solid waste, crushing it and passing it through a 60-mesh sieve to obtain a mixed solid waste powder; using a magnetic separator to perform magnetic separation on the powder; and then using a washing liquid to wash it to remove iron oxide and heavy metal ions therein, to obtain a pretreated solid waste powder;
[0008] S2, placing the pretreated solid waste powder in an ultrasonic melting furnace, using a 700-type molybdenum electrode to increase the temperature of the system to 800-1000°C at a heating rate of 10°C / min in the ultrasonic melting furnace, and then performing ultrasonic treatment for 30 minutes, then stopping the ultrasound and continuing the heat treatment for 1 hour, treating the flue gas generated in the process, and obtaining a solid waste heat treatment system;
[0009] S3, heating the solid waste heat treatment system to a molten state, and then testing the molten slurry. After passing the test, the molten slurry is introduced into a roller of a spinning machine. Under the action of high-speed centrifugal force, the slurry forms a thin layer of slurry on the surface of the centrifugal roller and extends outward into fiber filaments. The fiber filaments are placed in an ultrasonic bath filled with a gel precursor solution for ultrasonic treatment for 1 hour, and then ammonia water is added to the system to adjust the pH value of the system to 8-8.5, and then the system temperature is increased to 40-50°C, and the system is allowed to stand for 24 hours to gel. After draining the excess gel, it is placed in tert-butanol and soaked for 72 hours, and the tert-butanol is replaced every 24 hours. Then the fiber is pre-cooled at minus 18°C for 12 hours, and then freeze-dried at minus 30°C for 24 hours to obtain aluminum silicate fiber;
[0010] S4. The aluminum silicate fiber obtained in step S3 is input into the needle punching system for double-sided needle punching, followed by double-sided trimming, and the scraps are collected and sent into the vibrating screen for dispersion and reuse. The aluminum silicate fiber cotton after needle punching is sent to the automatic rolling system for rolling, bagging, and sealing operations, thereby obtaining a solid and hazardous waste collaborative resource utilization to produce aluminum silicate fiber cotton.
[0011] Furthermore, in step S1, the molar ratio of Al:Si in the composite solid waste is 2:1.
[0012] Furthermore, in step S1, the composite solid waste is composed of fly ash, slag coarse sand, bauxite slag and coal gangue in a ratio of (0.1-0.5):(0.1-0.5):(0.01-0.2):(0.1-0.5).
[0013] Furthermore, in step S1, the eluent is obtained by mixing 0.1-0.5 mol / L of organic acid and 0.05 mol / L of EDTA in any ratio; the elution conditions are that the solid-liquid ratio of the eluent to the sample to be washed is 1:10, the pH value of the eluent is 4, and the elution time is 4-6 hours.
[0014] Furthermore, in step S2, the specific operation of treating the flue gas is:
[0015] High-temperature denitrification treatment will be carried out, and the flue gas will be collected using a collection hood after waste heat utilization, and then enter the bag filter for wet deacidification again. After the low-temperature clean flue gas is heated to ≥180°C, it enters the high-temperature flue gas heat exchanger for heat exchange with the high-temperature flue gas, and is heated to above 230°C by the heater before entering the SCR reactor. After ammonia injection for denitrification treatment, it enters the 60-meter chimney to achieve ultra-low emissions.
[0016] Furthermore, in step S3, the specific operation of detecting the molten slurry is:
[0017] After the furnace is started, the first magma body is sampled and tested for melt acid leaching toxicity and melt water leaching toxicity. The test is conducted once a day. If the ash body, additive composition and formula remain unchanged, the sample is tested for composition for two consecutive months without change. Thereafter, samples are taken at the beginning and end of each month. If there is no change in the test for one year of continuous production, samples are taken at the end of each month.
[0018] Further, in step S3, the gel precursor solution is prepared by the following steps:
[0019] 9.0 mL of ethanol and 17.6 mL of deionized water were added into the container, followed by 3.452 g of hexadecyltrimethylammonium bromide. After stirring at room temperature for 30 minutes, a composite silane coupling agent was added. After continuing to stir for 30 minutes, a 0.1 mol / L hydrochloric acid solution was used to adjust the pH value of the system to 5.5-6. After reacting for 2 hours, a gel precursor solution was obtained.
[0020] Furthermore, the composite silane coupling agent is obtained by mixing any one of methylfluorosilane and ethylfluorosilane with methyltriethoxysilane in a mass ratio of (6-8):(10-12).
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] In the technical solution of the present invention, the volume of solid wastes such as fly ash is greatly reduced by preparing aluminum silicate fiber cotton from fly ash, slag coarse sand, bauxite slag and coal gangue solid wastes through a melting method. Through reasonable raw material ratios and efficient treatment methods, the melting temperature can be reduced, heavy metal gasification can be reduced, the solidification capacity of the magma body can be increased, and the energy consumption per ton can be reduced. The fiber products produced fully meet the national standards for thermal insulation cotton, and waste water and waste residue are all recycled and reused. The flue gas is also treated by multiple systems to achieve ultra-low emissions, which is conducive to the recycling and reuse of solid waste.
[0023] By using high temperature treatment combined with ultrasonic treatment, ultrasonic treatment increases the shear force generated during the heat treatment process, reduces the heat energy required for the solid waste to be converted into a molten state, and ultrasound increases the nucleation sites during the melting process and allows Si-O to break quickly to complete the transformation of Si atoms from α-quartz to β-quartz phase in the system in advance. The grain refinement of the product becomes higher and the viscosity of the melt is reduced, so that the system quickly generates mullite and corundum crystals to form aluminum silicate. By adjusting the solid waste components and high temperature treatment methods, the proportion of mullite and corundum crystals in the system is increased, the stress generated during the quartz formation process is reduced, and the high temperature treatment is ended as quickly as possible to prevent the problem of high brittleness of the final fiber product due to the increase of crystallization and the growth of crystals.
[0024] Furthermore, by using a polysilicon source including methylfluorosilane and methyltriethoxysilane to treat the obtained aluminum silicate fiber and then freeze-drying it, the use of heat energy to perform a thermosetting treatment on the aluminum silicate fiber is avoided, and the second flue gas treatment generated in the process is omitted; the acidic substance in the gel precursor solution will convert the residual impurities into soluble salts, which will be eliminated during the solution replacement process, and the hygroscopicity of the aluminum silicate fiber will be used to increase the adhesion of the gel on its surface, and then freeze-drying will be performed to form a layer of flexible SiO2 aerogel. Methylfluorosilane and ethylfluorosilane can extend the linear structure of Si-O-Si in the aerogel, increase the flexibility of the gel, improve its toughness and softness, and can give the SiO2 flexible aerogel hydrophobicity. That is, the softness of the obtained aluminum silicate fiber cotton can be improved, and the probability of its quality reduction such as slag falling and breakage can be reduced; its hydrophobicity can also be improved, and the problem of easy moisture absorption leading to reduced thermal insulation performance can be changed. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The reagents used in the following examples and comparative examples are all of analytical grade, and the component contents of the fly ash, slag grit, bauxite slag and coal gangue used are shown in Table 1 below.
[0027] Table 1 Component contents of fly ash, slag grit and coal gangue
[0028]
[0029] Example 1
[0030] The gel precursor solution was prepared by the following steps:
[0031] Methylfluorosilane and methyltriethoxysilane were mixed in a mass ratio of 6:10 to obtain a composite silane coupling agent, which was stored for later use; 9.0 mL of ethanol and 17.6 mL of deionized water were then added to the container, followed by 3.452 g of hexadecyltrimethylammonium bromide, and after stirring at room temperature for 30 minutes, 18 mL of the composite silane coupling agent was added, and after continuing to stir for 30 minutes, a 0.1 mol / L hydrochloric acid solution was used to adjust the pH value of the system to 5.5, and a gel precursor solution was obtained after reacting for 2 hours. Example
[0032] The difference between this embodiment and embodiment 1 is that the composite silane coupling agent in this embodiment is obtained by mixing ethyl fluorosilane and methyl triethoxysilane in a mass ratio of 11:7. The pH value of the gel precursor solution is adjusted to 5.8. Example
[0033] The difference between this embodiment and embodiment 1 is that the composite silane coupling agent in this embodiment is obtained by mixing methylfluorosilane and methyltriethoxysilane in a mass ratio of 12:8. The pH value of the gel precursor solution is adjusted to 6. Example
[0034] A method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous wastes comprises the following steps:
[0035] S1. Fly ash, slag coarse sand, bauxite slag and coal gangue are mixed in a ratio of 0.1:0.1:0.01:0.1 to obtain a composite solid waste; the composite solid waste is compounded in a process, then crushed and passed through a 60-mesh sieve to obtain a mixed solid waste powder; the powder is subjected to magnetic separation using a magnetic separator; then 0.1 mol / L citric acid and 0.05 mol / L EDTA are mixed to prepare an eluent, the pH value of the eluent is adjusted to 4, and the eluent is used for elution, the solid-liquid ratio of the eluent to the sample to be washed is 1:10, and the elution time is 4-6 hours to remove iron oxide and heavy metal ions therein, so as to obtain a pretreated solid waste powder.
[0036] S2. Place 1000g of pre-treated solid waste powder in an ultrasonic melting furnace, use a 700-type molybdenum electrode to increase the temperature of the system to 800℃ at a heating rate of 10℃ / min in the ultrasonic melting furnace, and then perform ultrasonic treatment for 30 minutes, then stop the ultrasound and continue the heat treatment for 1 hour, treat the flue gas generated in the process, and obtain a solid waste heat treatment system; wherein, the specific operation of the flue gas treatment is: high-temperature denitrification treatment, and the flue gas is collected using a collection hood after waste heat utilization, and then enters the bag filter and wet deacidification again. After the low-temperature clean flue gas is heated to a temperature of ≥180℃, it enters the high-temperature flue gas heat exchanger for heat exchange with the high-temperature flue gas, and then is heated to above 230℃ by the heater and enters the SCR reactor. After ammonia injection denitrification treatment, it enters the 60-meter chimney to complete ultra-low emissions.
[0037] S3, heating the solid waste heat treatment system to a molten state, and then testing the molten slurry. After passing the test, the molten slurry is introduced into a roller of a spinning machine. Under the action of high-speed centrifugal force, the slurry forms a thin layer of slurry on the surface of the centrifugal roller and extends outward into fiber filaments. The fiber filaments are placed in an ultrasonic bath filled with a gel precursor solution for ultrasonic treatment for 1 hour, and then ammonia water is added to the system to adjust the pH value of the system to 8, and then the system temperature is increased to 40°C, and the system is allowed to stand for 24 hours to gel. After draining the excess gel, it is placed in tert-butanol for 72 hours, and the tert-butanol is replaced every 24 hours. Then the fiber is pre-cooled at minus 18°C for 12 hours, and then freeze-dried at minus 30°C for 24 hours to obtain aluminum silicate fiber;
[0038] S4. The aluminum silicate fiber obtained in step S3 is input into the needle punching system for double-sided needle punching, followed by double-sided trimming, and the scraps are collected and sent into the vibrating screen for dispersion and reuse. The aluminum silicate fiber cotton after needle punching is sent to the automatic rolling system for rolling, bagging, and sealing operations, thereby obtaining a solid and hazardous waste collaborative resource utilization to produce aluminum silicate fiber cotton. Example
[0039] The difference between this embodiment and embodiment 4 is that in step S1, the composite solid waste is obtained by mixing fly ash, slag coarse sand, bauxite slag and coal gangue in a ratio of 0.3:0.2:0.1:0.2; the elution liquid is obtained by mixing 0.3 mol / L citric acid and 0.05 mol / L EDTA, and the elution time is 5 hours. In step S2, the temperature in the ultrasonic melting furnace is 900°C. In step S3, ammonia water is used to adjust the pH value of the system to 8.3, and the system temperature is increased to 45°C to make it gel. Example
[0040] The difference between this embodiment and embodiment 4 is that in step S1, the composite solid waste is obtained by mixing fly ash, slag coarse sand, bauxite slag and coal gangue in a ratio of 0.5:0.5:0.2:0.5; the elution liquid is obtained by mixing 0.5 mol / L citric acid and 0.05 mol / L EDTA, and the elution time is 5 hours. In step S2, the temperature in the ultrasonic melting furnace is 1000°C. In step S3, ammonia water is used to adjust the pH value of the system to 8.5, and the system temperature is increased to 50°C to make it gel.
[0041] Comparative Example 1
[0042] The difference between this comparative example and Example 5 is that ultrasonic treatment is not used in step S2, and the pretreated solid waste powder is directly heated to a molten state.
[0043] Comparative Example 2
[0044] The difference between this comparative example and Example 5 is that in steps S3 and S4, the solid waste heat treatment system is heated to a molten state, and then the molten slurry is tested. After passing the test, the molten slurry is introduced into a roller of a spinning machine, and under the action of high-speed centrifugal force, the slurry forms a thin layer of slurry on the surface of the centrifugal roller and extends outward into fiber filaments; the fiber filaments are input into the needle punching system for double-sided needle punching, and then double-sided trimming is performed, and the scrap materials are collected and sent to the vibrating screen for dispersion and reuse, and the cotton felt after needle punching is sent to the drying system, and is baked and shaped at 500-720°C in the hot air zone composed of electric heating rods, and then sent to the automatic rolling system for rolling, bagging, and sealing operations, so as to obtain a kind of aluminum silicate fiber cotton produced by the coordinated resource utilization of solid and hazardous waste.
[0045] The fiber wool prepared in Examples 4-6 and Comparative Examples 1-2 was tested for performance. The thermal insulation performance was tested using the guarded hot plate method in GB / T10294 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials"; the hygroscopic performance was tested using the test method specified in Part 7 of GB / T5480.7 "Test Methods for Mineral Wool and Its Products" for hygroscopicity; five readings were obtained for each sample and the average value was taken. The test results are shown in Table 1 below.
[0046] Table 1 Performance test of fiber cotton prepared in Examples 4-6 and Comparative Examples 1-2
[0047]
[0048] From the results in Table 1, it can be seen that the fiber cotton prepared in Example 6 has the highest thermal conductivity and the lowest moisture absorption rate. From the results in Comparative Example 1, it can be seen that ultrasonic treatment can improve the grain fineness of each component in the system, increase the number of mass transfers in the thermal scattering process, and make it have better thermal insulation effect. From the results in Comparative Example 2, it can be seen that using an aerogel layer to strengthen the fiber can improve its thermal insulation performance and hydrophobicity.
[0049] The mechanical properties of the fiber wool prepared in Examples 5-7 and Comparative Examples 1-2 were tested using the test method specified in GB / T30804 "Determination of tensile strength perpendicular to the surface of thermal insulation products for building use". The test results are shown in Table 2.
[0050] Table 2 Test of mechanical properties of fiber cotton prepared in Examples 5-7 and Comparative Examples 1-2
[0051]
[0052] From the results in Table 2, it can be seen that the aluminum silicate fiber cotton prepared in Example 6 has the highest mechanical properties. From the data in Comparative Examples 1 and 2, it can be seen that the use of ultrasonic treatment technology in the preparation process can refine the grains, increase the number of grains per unit volume, and disperse the deformation amount to more grains when deformation occurs, resulting in uniform changes, reducing stress concentration, improving the mechanical properties of the fiber cotton, and improving its toughness and tensile strength. The use of SiO2 aerogel layer can also improve its mechanical properties including compressive strength and tensile strength.
[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous wastes, characterized in that: The following steps are involved: S1. Compounding the composite solid waste, crushing it and passing it through a 60-mesh sieve to obtain a mixed solid waste powder; using a magnetic separator to perform magnetic separation on the powder; and then using a washing liquid to wash it to remove iron oxide and heavy metal ions therein, to obtain a pretreated solid waste powder; S2, placing the pretreated solid waste powder in an ultrasonic melting furnace, raising the system temperature to 800-1000°C at a heating rate of 10°C / min, and then performing ultrasonic treatment for 30 minutes, then stopping the ultrasound and continuing the heat treatment for 1 hour, treating the flue gas generated in the process, and obtaining a solid waste heat treatment system; S3, heating the solid waste heat treatment system to a molten state, and then testing the molten slurry. After passing the test, the molten slurry is introduced into a roller of a spinning machine. Under the action of high-speed centrifugal force, the slurry forms a thin layer of slurry on the surface of the centrifugal roller and extends outward into fiber filaments. The fiber filaments are placed in an ultrasonic bath filled with a gel precursor solution for ultrasonic treatment for 1 hour, and then ammonia water is added to the system to adjust the pH value of the system to 8-8.5, and then the system temperature is increased to 40-50°C, and the system is allowed to stand for 24 hours to gel. After draining the excess gel, it is placed in tert-butanol and soaked for 72 hours, and the tert-butanol is replaced every 24 hours. Then the fiber is pre-cooled at minus 18°C for 12 hours, and then freeze-dried at minus 30°C for 24 hours to obtain aluminum silicate fiber; S4, the aluminum silicate fiber obtained in step S3 is input into the needling system for double-sided needling, followed by double-sided trimming, the scraps are collected and sent to the vibrating screen for dispersion and reuse, and the aluminum silicate fiber cotton after needling is sent to the automatic rolling system for rolling, bagging, and sealing operations, thereby obtaining a solid and hazardous waste collaborative resource utilization production aluminum silicate fiber cotton; In step S1, the composite solid waste is composed of fly ash, slag coarse sand, bauxite slag and coal gangue in a ratio of (0.1-0.5): (0.1-0.5): (0.01-0.2): (0.1-0.5); In step S3, the gel precursor solution is prepared by the following steps: Add ethanol and deionized water into a container, then add hexadecyltrimethylammonium bromide, stir at room temperature for 30 minutes, then add the composite silane coupling agent, continue stirring for 30 minutes, adjust the pH value of the system to 5.5-6, and react for 2 hours to obtain a gel precursor solution; The composite silane coupling agent is obtained by mixing any one of methyl fluorosilane and ethyl fluorosilane with methyl triethoxysilane in a mass ratio of (6-8): (10-12).
2. The method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous waste according to claim 1, characterized in that: In step S1, the molar ratio of Al:Si in the composite solid waste is 2:
1.
3. The method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous waste according to claim 1, characterized in that: In step S1, the eluent is obtained by mixing 0.1-0.5 mol / L of organic acid and 0.05 mol / L of EDTA in any ratio; the elution conditions are that the solid-liquid ratio of the eluent to the sample to be washed is 1:10, the pH value of the eluent is 4, and the elution time is 4-6 hours.
4. The method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous waste according to claim 1, characterized in that: In step S2, the specific operation of treating the flue gas is as follows: High-temperature denitrification treatment will be carried out, and the flue gas will be collected using a collection hood after waste heat utilization, and then enter the bag filter for wet deacidification again. After the low-temperature clean flue gas is heated to ≥180°C, it enters the high-temperature flue gas heat exchanger for heat exchange with the high-temperature flue gas, and is heated to above 230°C by the heater before entering the SCR reactor. After ammonia injection for denitrification treatment, it enters the 60-meter chimney to achieve ultra-low emissions.
5. The method for producing aluminum silicate fiber cotton by collaborative resource utilization of solid and hazardous wastes according to claim 1, characterized in that: In step S3, the specific operation of detecting the molten slurry is: After the furnace is started, the first magma body is sampled and the acid leaching toxicity and water leaching toxicity of the melt are tested once a day. Under the condition that the ash body, auxiliary agent composition and formula remain unchanged, sampling is carried out for two consecutive months without any change in composition. Thereafter, samples are taken at the beginning and end of each month. After one year of continuous production, there is no change in the test, and sampling is taken at the end of each month thereafter.
Citation Information
Patent Citations
Aluminum silicate fibers and aluminum silicate fiber needle felt and preparation method thereof
CN109735961A
Preparation method of heat-resistant fiber reinforced silicon dioxide aerogel composite material
CN115925383A
Cited By
Coal-based solid waste fiber forming process technological parameter self-adaptive control system and control method
CN121454955A